Medieval East Anglia - Harper-Bill, Christopher (Boydell Press, 2005)
"Medieval East Anglia - one of the most significant and prosperous parts of England in the middle ages - examined through essays on its landscape, history, religion, literature, and culture"--Provided by publisher